Action Research in Education: Learning Through Practitioner Enquiry (IInd Edition) - Pal, Rajendra; Gupta, Sakshi (INDIAN EDUCATIONAL REVIEW, 2013)
The book under review “Action Research in Education” is a professional book to find out more about the process of enquiry in the professional practice of teachers. The price of the book (R 2400 soft bind) is slightly higher for a reader to purchase. The IInd edition of the book contains wider range of real life case studies and composite examples drawn from teaching practice. In today’s scenario it is evident that research by practitioner is an essential activity and it is increasing day by day for improvement in their practical life. The book gives advice’s to make research more fruitful and sophisticated. Every chapter of this book contains separate bibliography, which would help new researcher to go through the further references. Index given at the end of the book is very helpful for quick search of the desired concept.